Romani routes : cultural politics and Balkan music in diaspora. - Silverman, Carol (Oxford University Press, 2014)
Over the past two decades, a steady stream of recordings, videos, feature films, festivals, and concerts has presented the music of Balkan Gypsies, or Roma, to Western audiences, who have greeted them with exceptional enthusiasm. Yet, as author Carol Silverman notes, "Roma are revered as musicians and reviled as people." In this book, Silverman introduces readers to the people and cultures who produce this music, offering a sensitive and incisive analysis of how Romani musicians address the challenges of discrimination. Focusing on southeastern Europe then moving to the diaspora, her book examines the music within Gypsy communities, the lives and careers of outstanding musicians, and the marketing of music in the electronic media and "world music" concert circuit. Silverman touches on the way that the Roma exemplify many qualities—adaptability, cultural hybridity, transnationalism—that are taken to characterize late modern experience. Rather than just celebrating these qualities, she presents the musicians as complicated, pragmatic individuals who work creatively within the many constraints that inform their lives - Présentation de l'éditeur.